Basal Vascular Smooth Muscle Cell Tone in eNOS Knockout Mice Can Be Reversed by Cyclic Stretch and Is Independent of Age - De Moudt, Sofie; Hendrickx, Jhana O.; De Meyer, Guido R. Y.; Martinet, Wim; Fransen, Paul (Frontiers in Physiology, 2022)
Introduction and Aims. Endothelial nitric oxide synthase (eNOS) knockout mice develop pronounced cardiovascular disease. In the present study, we describe the alterations in aortic physiology and biomechanics of eNOS knockout and C57Bl/6 control mice at 2 to 12 months of age, including a thorough physiological investigation of age and cyclic stretch-dependent VSMC contractility and aortic stiffness. Methods and Results. Peripheral blood pressure and aortic pulse wave velocity were measured in vivo, and aortic biomechanical studies and isometric contractions were investigated ex vivo. Age-dependent progression of aortic stiffness, peripheral hypertension, and aortic contractility in eNOS knockout mice was absent, attenuated, or similar to C57Bl/6 control mice. Voltage-gated calcium channel (VGCC)-dependent calcium influx inversely affected isometric contraction and aortic stiffening by α1-adrenergic stimulation in eNOS knockout mice. Baseline aortic stiffness was selectively reduced in eNOS knockout mice after ex vivo cyclic stretch exposure in an amplitude-dependent manner, which prompted us to investigate cyclic stretch dependent regulation of aortic contractility and stiffness. Aortic stiffness, both in baseline conditions and after activation of vascular smooth muscle cell (VSMC) contraction, was reduced with increasing cyclic stretch amplitude. This cyclic stretch dependency was attenuated with age, although old eNOS knockout mice displayed better preservation of cyclic stretch-dependency compared to C57Bl/6 control mice. Store operated calcium entry-medicated aortic stiffening as induced by inhibiting sarcoplasmic reticulum calcium ATPase pumps with 10 µM CPA was most pronounced in the aorta of aged mice and at low cyclic stretch amplitude, but independent of eNOS. Basal aortic tonus and VSMC depolarization were highly dependent on eNOS, and were most pronounced at low cyclic stretch, with attenuation at increasing cyclic stretch amplitude. Conclusion. eNOS knockout mice display attenuated progression of arterial disease as compared to C57Bl/6 control mice. Basal VSMC tone in eNOS knockout mice could be reduced by ex vivo exposure to cyclic stretch through stretch-dependent regulation of cytosolic calcium. Both baseline and active aortic stiffness were highly dependent on cyclic stretch regulation, which was more pronounced in young versus old mice. Other mediators of VSMC contraction and calcium handling were dependent on cyclic stretch mechanotransduction, but independent of eNOS.